Educational Practices and Child Behaviors: Mothers’ and Teachers’ Evaluation - Bolsoni-Silva, Alessandra Turini [UNESP]; Loureiro, Sonia Regina (FapUNIFESP (SciELO), 2021)
– The objective of this study was to describe and compare mothers’ and teachers’ reports concerning their educational social skills and negative practices and children’s behavioral problems and social skills. The mothers and teachers of 81 children participated in this study. The children were assigned to four groups depending on whether they presented problems exclusively at home, school, in both, or none of these contexts. Valid instruments measured educational practices and child behavior. The results show that: (a) mothers and teachers agreed that children with problems in both contexts presented the highest level of impairment; (b) the mothers more frequently reported skills such as affection, adopted negative practices, and identified problem behaviors; (c) the teachers reported more skills such as limit setting. The conclusion is that teachers’ and mothers’ practices differ, and such information can guide preventive programs and interventions.
Práticas Educativas e Comportamentos Infantis: Avaliações de Mães e Professores
Keywords: educational practices; escola; family; família; habilidades sociais; problem behavior; problemas de comportamento; práticas educativas; school; social skills